Dissatisfied with Life or with Being Interviewed? Happiness and Motivation to Participate in a Survey - Adrian Chadi (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Information on the number of interviewer contacts allows insights into how people's responses to questions on happiness are connected to the difficulty of reaching potential participants. Using the paradata of the German Socio-Economic Panel Study (SOEP), this paper continues such research by revealing a strong link between respondent motivation and reported happiness. Analyses of responses by future non-respondents substantiate this finding and shed light on a key question for empirical research on subjective well-being, which is whether the unhappy tend to avoid survey participation or whether the unwilling might respond more negatively when being asked about their satisfaction with life.
Keywords: C80; I30; Z00; 330